Effect of urban area development in Negeri Sembilan to the Air Pollution Index from 2012 to 2014 - Ahmad Fauzi, Farah Nor Insyirah (2019)
Air pollution Index (API) in Malaysia is used to determine the air quality in the surrounding. Based on the Malaysian Department of the Environment (DOE), five parameter that been used for API are particulate matter <10μm (PM10), ozone (O3), carbon monoxide (CO), Sulphur dioxide (SO2), and nitrogen dioxide (NO2). A study of the API parameter in Negeri Sembilan from 2012 to 2104 was performed to know the trend of air quality in Negeri Sembilan. Two district representative the air quality in Negeri Sembilan which are Nilai and Ampangan. Studied area of these two selected district and analysed the trend of the parameter from data of DOE were applied for this study. The result for the highest value for each parameter in Ampangan from 2012 to 2014 for concentration of SO2, NO2, O3, CO and PM10 were at value 0.007 ppm, 0.029 ppm, 0.096 ppm, 2.56 ppm and 177 µg/m3 respectively. Meanwhile in Nilai, the highest value for each parameter concentration of SO2, NO2, O3, CO and PM10 resulting at value 0.012 ppm, 0.045 ppm, 0.076 ppm, 2.19 ppm and 202 µg/m3 respectively. The trend show that SO2, NO2 and PM10 concentration in Nilai has higher than in Ampangan. Meanwhile, concentration O3 and CO in ambient air in Ampangan was higher than air in Nilai. This happened due to the increasing of population in Ampangan and the number of industry in Nilai within the three years. Besides, haze episode from Kalimantan, Indonesia and peatland fires in Peninsular Malaysia also resulted unhealthy level of air quality in Negeri Sembilan on 2013 and 2014